EFEKTIVITAS PEMBAYARAN PAJAK ORANG PRIBADI SECARA ELEKTRONIK (E-BILLING) DI KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU TAMPAN - Ningsih, Tria; Tua RFS, Harapan Tua, RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Taxation in Indonesia has experiencing rapid development. It is evidenced by the existence of a reform in the payment of the tax that was previously using manual methods and proceed with e-billing. E-billing is one innovation made by the Directorate General of Taxing in the field of tax payment. Payment reform is expected to facilitate taxpayer to make tax payment, Because taxpayesr do not have to come to tax office. The purpose of this research to find out effectiveness of electronic personal tax payments (e-billing) and factor inhibiting of Effectiveness of Electronic Personal Tax Payments (e-billing) at the Tax Services Office Pratama Pekanbaru Tampan. The theory used in this research is theory of the effectiveness of Duncan cited by Steers (2008:53), with indicators : Achievement of goals, Integration, Adaptation. The research methods used is the qualitative descriptive with case study. Selection of informants using the purposive sampling method. The data collection through interviews, observations and documentation. This research result that the payment of electronic personal tax (e-billing) at the Tax Services Office Pratama Pekanbaru Tampan has been not effectively measured based on 3 (three) indicators that are Achievement of goals, Integration, and Adaptation. Inhibiting factors of Effectiveness of Electronic Personal Tax Payments (e-billing) at the Tax Services Office Pratama Pekanbaru Tampan is down the server, network connection and the existence of technological gaps among taxpayers. Â * Keywords : e-billing, Tax Payment System, Effectiveness